Tanggap fungsional Menochilus sexmaculatus Fabricius (Coleoptera: Coccinellidae) terhadap Aphis gossypii (Glover) (Homoptera: Aphididae) pada umur tanaman cabai berbeda - Novri Nelly; Trizelia Trizelia; Qorry Syuhadah (Jurnal Entomologi Indonesia, 2012)
The lady beetle, Menochilus sexmaculatus is one of the biological control agents that can be used to control aphids. Presently, there is a lack of information about the effectiveness of this beetle to control aphids. The objective of this research was to study the functional response of M. sexmaculatus on Aphis gossypii at different ages of plants. All preys were exposed to one M. sexmaculatus adult for an hour at five different densities of aphids (10, 20, 30, 40, and 50 individuals) is four different ages of chilli plants (2,4,6, and 8 weeks). Data were analyzed by ANOVA and logistic regression to determine the type of functional response. The results showed that the ability of M. sexmaculatus to prey was not significant at 2 to 4 and 6 to 8 weeks old chilli plants. At 2 week old chilli plants M. sexmaculatus showed type I of functional response, while at 4, 6 and 8 weeks the functional response were type III.